Implementasi Pendekatan Deep Learning Dalam Meningkatkan Mutu Pendidikan di Tingkat Dasar - Nainggolan, Risnawati (Yayasan Darussalam Bengkulu, 2025)
The quality of education at the elementary school level is a crucial foundation for developing students' cognitive abilities, character, and 21st-century competencies. In line with the implementation of the Independent Curriculum, the deep learning approach is a learning strategy that emphasizes in-depth conceptual understanding, critical and reflective thinking, and the connection of knowledge to real-life contexts. This study aims to examine the implementation of the deep learning approach in improving the quality of education at the elementary level and identify challenges in its implementation. The method used was library research, analyzing scientific journals, academic books, educational regulations, and relevant official documents. The study results indicate that the deep learning approach, through the integration of meaningful, mindful, and joyful learning, can improve the quality of learning processes and outcomes and support students' achievement of global competencies. However, its implementation still faces obstacles, particularly in teacher readiness, limited practical training, student developmental characteristics, and supporting facilities and infrastructure. Therefore, systemic and sustainable support is needed for optimal implementation of deep learning in improving the quality of elementary education.